Pseudoternary Phase Diagram and Antibacterial Activity of Microemulsion-Based Citronella Oil - Gunarto, Chintya; Go, Alchris Woo; Angkawijaya, Artik Elisa; Lie, Jenni; Soetaredjo, Felycia Edi; Ismadji, Suryadi; Puspitasari, Nathania; Putro, Jindrayani Nyoo; Risdian, Chandra (Universitas Gadjah Mada, 2024)
Citronella oil (CTO) is extracted from citronella leaves by maceration or steam distillation process, which has antibacterial and insect-repellent activities. However, the use of CTO is limited and requires modification in other formulations, such as microemulsion (ME), to increase its bioactivities. ME consists of oil, water, surfactant and/or cosurfactant and is commonly applied in food and beverages, cosmetics, and carrier for drug delivery applications. CTO was used as the oil phase for ME with nonionic surfactant and ethanol as a cosurfactant for lowering interfacial tension between oil and water phase. Subsequent observations regarding stability and antibacterial tests were carried out on ME formulations with surfactant/cosurfactant mixture of 2 due to its largest ME area. A hydrodynamic diameter analysis was also carried out to see the stability of the ME within a period of 50 d. ME with 10% CTO, 30% surfactant mixture, and 60% water showed the best formulation observed from the consistent hydrodynamic diameter measurement. In addition, ME with different formulations could inhibit the growth of Escherichia coli and Staphylococcus aureus by more than 90%. From this research, CTO-based ME potentially improve and develop drug carrier applications, especially via topical route.